(NtABLICY a(B. (Ni(B. (NpETROSQNCA PO INSTRUMENTOWEDENI@ W PRAKTIKE MUZYKALXNOGO(B.s (N~OLGULA[TIRI[(B.s - (NbOKIDVON rAHIMDVONOW(B.s ((NtA[KENTs, 2005)
(Nw(B. (NdANNOE RABOTE RASKRYWAETSQ SODERVANIE TABLIC a(B. (Ni(B. (NpETROSQNCA(B.s
Keywords: 9